Interplay between stress and cancer—A focus on inflammation - Vignjević Petrinović, Sanja; Milošević, Maja S.; Marković, Dragana; Momčilović, Sanja (Frontiers in Physiology, 2023)
Stress is an integral part of life. While acute responses to stress are generally regarded as beneficial in dealing with immediate threats, chronic exposure to threatening stimuli exerts deleterious effects and can be either a contributing or an aggravating factor for many chronic diseases including cancer. Chronic psychological stress has been identified as a significant factor contributing to the development and progression of cancer, but the mechanisms that link chronic stress to cancer remain incompletely understood. Psychological stressors initiate multiple physiological responses that result in the activation of the hypothalamic-pituitary-adrenal (HPA) axis, sympathetic nervous system, and the subsequent changes in immune function. Chronic stress exposure disrupts the homeostatic communication between the neuroendocrine and immune systems, shifting immune signaling toward a proinflammatory state. Stress-induced chronic low-grade inflammation and a decline in immune surveillance are both implicated in cancer development and progression. Conversely, tumor-induced inflammatory cytokines, apart from driving a tumor-supportive inflammatory microenvironment, can also exert their biological actions distantly via circulation and therefore adversely affect the stress response. In this minireview, we summarize the current findings on the relationship between stress and cancer, focusing on the role of inflammation in stress-induced neuroendocrine-immune crosstalk. We also discuss the underlying mechanisms and their potential for cancer treatment and prevention.